COVID-19 in the Pediatric Population: What We Have Learned About Its Clinical Presentation and Diagnosis - Luis Ignacio Perez-Velazquez; Fernanda Edith Villanueva; Michelle Arias Gonzales; Gilberto Flores-Vargas; Maria de Jesus Gallardo-Luna; Efrain Navarro-Olivos; Ligia Gricelda Arce-Padilla; Nicolas Padilla-Raygoza (Recent Updates in Disease and Health Research Vol. 8, 2024)
COVID-19, an acute respiratory disease caused by SARS-CoV-2, was first identified in Wuhan, China in December 2019 due to cases of atypical pneumonia and quickly spread globally, being declared a pandemic by the World Health Organization in March 2020. Since its emergence, knowledge about its clinical presentation, especially in children, has evolved significantly. This article reviews the most recent literature to provide an updated perspective on the epidemiology of COVID-19 in children, its transmission mechanisms, typical and atypical clinical presentations, and the diagnostic approaches employed. It highlights that although children generally exhibit milder symptoms compared to adults, atypical manifestations and associated syndromes such as multisystem inflammatory syndrome in children (MIS-C) can pose significant diagnostic and therapeutic challenges.